2015
DOI: 10.1002/cbic.201402650
|View full text |Cite
|
Sign up to set email alerts
|

A Photorhabdus Natural Product Inhibits Insect Juvenile Hormone Epoxide Hydrolase

Abstract: Simple urea compounds (“phurealipids”) have been identified from the entomopathogenic bacterium Photorhabdus luminescens, and their biosynthesis was elucidated. Very similar analogues of these compounds have been previously developed as inhibitors of juvenile hormone epoxide hydrolase (JHEH), a key enzyme in insect development and growth. Phurealipids also inhibit JHEH, and therefore phurealipids might contribute to bacterial virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…methyl isocyanate ( Figure S7). These resultss how that the chain length tolerance for the incorporation of AFAs is narrower than that for phenethylamides, which correlates well with previousf indings [18] showing the incorporation of C 9 to C 14 alkyl chains in phurealipids. Since in the presentw ork 10 a and 10 d were only detected in trace amounts, it can be concluded that the preferred chain length forA FAsi nt his case is C 9 or C 10 (9b and 9c), whichi si na ccordance with the main natural products if the azide group is regarded as being equivalent in size to an ethyl group rathert han ap ropyl group due to its greater rigidity.…”
Section: Carr Enrichment Of Azidof Atty Acids and Natural Products Desupporting
confidence: 92%
“…methyl isocyanate ( Figure S7). These resultss how that the chain length tolerance for the incorporation of AFAs is narrower than that for phenethylamides, which correlates well with previousf indings [18] showing the incorporation of C 9 to C 14 alkyl chains in phurealipids. Since in the presentw ork 10 a and 10 d were only detected in trace amounts, it can be concluded that the preferred chain length forA FAsi nt his case is C 9 or C 10 (9b and 9c), whichi si na ccordance with the main natural products if the azide group is regarded as being equivalent in size to an ethyl group rathert han ap ropyl group due to its greater rigidity.…”
Section: Carr Enrichment Of Azidof Atty Acids and Natural Products Desupporting
confidence: 92%
“…In line with these findings, chemical analysis revealed that the amount of other known secondary metabolites [isopropylstilbene (IPS), GameXPeptides (GXP), photopyrones (PPY) and phurealipids (PL)] [13, 22, 23, 24] is not significantly affected when comparing the wild type with Δ antJ and the complemented strain Δ antJ + antJ + (Fig. S3A).…”
Section: Resultssupporting
confidence: 59%
“…The gene encoding AntJ ( plu4185 ) was deleted using pCKcipB [24], which is a derivative of pDS132 [44]. For the in frame deletion of antJ an upstream (926 bp) and a downstream fragment (788 bp) of antJ were amplified by PCR using primers AKHp06–AKHp09 introducing a PstI and a BamHI restriction site to the 5′end of the upstream fragment and the 3′end of the downstream fragment, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Upregulation of all PLs also could be seen in ΔluxS G in an additional analysis. PL biosynthesis also starts with fatty-acid-derived aldehydes (Nollmann et al, 2015). The role of spermidine in this process was concluded from reduced expression of several genes encoding proteins related to polyamine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…10 ml LB medium with or without 2% of Amberlite® XAD-16 (Sigma-Aldrich) (XAD) were inoculated with a starting OD 600 = 0.1 using an overnight culture. After 72 h of cultivation at 30°C either XAD or ethyl acetate (EE) culture extracts were prepared as described before (Nollmann et al, 2015;Heinrich et al, 2016) HPLC-UV/MS analysis was done as previously stated (Reimer et al, 2011). 5 µl of each sample was separated on a C 18 -UHPLC column (Acquity UPLC BEH C18 1.7 lmRP 2.1 x 50 mm (Waters)) with a C 18 -pre-column (Acquity UPLC BEH C18 1.7 lmRP 2.1 x 5 mm (Waters)) using a H 2 O in acetonitrile (ACN) gradient.…”
Section: Np Quantificationmentioning
confidence: 99%